2020
DOI: 10.1111/pai.13398
|View full text |Cite
|
Sign up to set email alerts
|

NovelPGM3compound heterozygous variants with IgE‐related dermatitis, lymphopenia, without syndromic features

Abstract: Background: Phosphoglucomutase-3 (PGM3) deficiency is a congenital disorder of glycosylation (CDG) with hyperimmunoglobulin IgE, atopy, and a variable immunological phenotype; most reported patients display dysmorphic features. The aim of the study was to characterize the genotype and phenotype of individuals with newly identified compound heterozygous variants in the phosphate-binding domain of PGM3 in order to better understand phenotypic differences between these patients and published cases. Methods: We an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Hypomorphic phosphoglucomutase 3 ( PGM3) mutations with autosomal recessive transmission cause abnormal protein glycosylation and differences in the cellular metabolism. The clinical presentation is characterized by high serum IgE, atopy, neurological impairment, immunodeficiency and autoimmunity ( 95 ). In fact, it was demonstrated that altered glycosylation due to PGM deficiency may also affect a subset of lymphocytes ( 96 , 97 ).…”
Section: Other Genesmentioning
confidence: 99%
“…Hypomorphic phosphoglucomutase 3 ( PGM3) mutations with autosomal recessive transmission cause abnormal protein glycosylation and differences in the cellular metabolism. The clinical presentation is characterized by high serum IgE, atopy, neurological impairment, immunodeficiency and autoimmunity ( 95 ). In fact, it was demonstrated that altered glycosylation due to PGM deficiency may also affect a subset of lymphocytes ( 96 , 97 ).…”
Section: Other Genesmentioning
confidence: 99%
“…Manifestations include elevated IgE, myoclonus, neurocognitive impairment, recurrent viral and pulmonary infections and an eczematous rash. 29 The cutaneous involvement may manifest similarly to those with atopy, including development of allergies and asthma. 30,31 IMMUNE DYSREGULATION POLYENDOCRINOPATHY ENTEROPATHY X-LINKED (IPEX)…”
Section: Wiskott-aldrich Syndromementioning
confidence: 99%
“…The validity of the disease categories derived from this exercise relies heavily on the continuous confirmation and updating of such phenotypic features. In this context, the virtual issue on “Inborn Errors of Immunity” aims at providing the readers of PAI a collection of topical reviews on some of the major immunological pathways that can be affected by pathological genetic variants causing IEIs and a selection of original articles highlighting clinical observations from cohort studies of well‐known conditions, as well as original discoveries that extend the genetic and clinical features of less commonly observed IEIs 1–17 …”
mentioning
confidence: 99%
“…In this context, the virtual issue on "Inborn Errors of Immunity" aims at providing the readers of PAI a collection of topical reviews on some of the major immunological pathways that can be affected by pathological genetic variants causing IEIs and a selection of original articles highlighting clinical observations from cohort studies of well-known conditions, as well as original discoveries that extend the genetic and clinical features of less commonly observed IEIs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In their review of IEIs caused by defects in the DNA damage response pathways, Fournier and Colleagues 3 Additional reviews of the areas of IEIs characterized by defects of actin cytoskeletal dynamics, the JAK-STAT pathways, and type I interferon disorders have been commissioned and will be available in the near future. These works will complement the current collection and provide the readers of PAI with additional timely updates and perspectives on the scientific and clinical aspects of some of the major disease subgroups in the field of IEIs.…”
mentioning
confidence: 99%